Living Qur’an of Kempekan at Pesantren Babakan Ciwaringin, Cirebon: Transmission and Transformation of the Qur’an Recitation - Hanan, Abdul (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2019)
This present study aims to explore the phenomenon of the Qur’an recitation by employing a ‘Kempekan’ model, which is transmitted at Pesantren (Islamic boarding school) Babakan. Kempekan is a style of tartil (a proper manner) recitation of the Qur’an promoted at Pesantren Kempek. A qualitative approach was designed in this ethnographic study. The data were collected through observation and interviews. The findings demonstrate two important points obtained from the living Qur’an of Kempekan. Firstly, the phenomenon of Kempekan which has emerged amid the pesantren not only to maintain the originality of the Qur’an recitation, but also to shape a new tradition of both its transmission and transformation patterns. It can be noticed from the development of the practice of today’s Qur’an recitation in Indonesia. Secondly, the surge of Kempekan has pervaded a plethora of cultural aspects occurring in Babakan. This can be evidenced from communities in the so-called Region III Cirebon, namely: Majalengka, Kuningan, Indramayu, and Cirebon, who attended the khatm al-Qur’an. The transmission and transformation of Kempekan raise the dialectical model of the Qur’an and its distinctive culture. The recitation of the Qur’an is not only limited to the rituals of ubuddiyah (religious merits), but also impacts on aspects of culture, economy, the structure of society, and a new model of piety.